Values Of Character Education: Study of Strengthening the Culture of Digital Literacy for Youth in Disruptive 5.0 Era - Nasar, Ismail; Nurdianingsih, Fitri; Rahmi, Elvi; Purwanto, Muhammad Bambang (Universitas Wiralodra, 2024)
This study aims to instill the values ​​of character education in strengthening the culture of digital literacy for teenagers at State Vocational Schools in Palembang City. This research uses educational, historical, and sociological approaches where research data is sourced from primary and secondary data from literature or reference books and documents as supporting data. The researchers were the essential instruments, and they then developed new instruments, namely observation guidelines, interview guidelines, and documentation. All three are used to collect data in the field. For this study, two main factors play a vital role in the reinforcement of the results of the data analysis study: supporting factors and inhibiting factors. The results of this study indicate that the values ​​of character education in strengthening the culture of digital literacy, which are carried out at State Vocational Schools in Palembang City, are still shallow, even though there are 15 minutes of extensive reading movements which are carried out every day but this is due to the lack of time allotted for the implementation of literacy culture. The character values ​​instilled in students are bright, honest, responsible, disciplined, and caring.